2015 IEEE 15th International Conference on Environment and Electrical Engineering (EEEIC) 2015
DOI: 10.1109/eeeic.2015.7165437
|View full text |Cite
|
Sign up to set email alerts
|

Geographic routing protocol for peer-to-peer smart grid neighborhood area network

Abstract: The distribution segment of the power system is of great importance in the smart grid (SG). The deployment of Information and Communication Technologies (ICTs) to support conventional grid will solve legacy problems that used to prevent implementation of smart services such as smart metering, Demand Side Management (DSM) or the integration of Distributed Energy Resources (DERs) within the SG. In this contribution, GRACO, a new geographic routing algorithm is proposed to support exploitation of SG full potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…There is no smart grid for all, every energy grid will develop its own applications and services. Therefore, many services and concepts related to smart grid such as Virtual Power Plant (VPP) [42] [43] and distributed energy and storage integration into the grid [44] are expected to require partial or fully distributed control and the ICT deployed in parallel to the electrical grid should be scalable and should not introduce additional constraints to the smart grid development. For this purpose, we plan to study and analyze the applications supported by NAN in order to define NAN communication requirements, and to implement an extension of GRACO that takes account of the QoS required.…”
Section: Resultsmentioning
confidence: 99%
“…There is no smart grid for all, every energy grid will develop its own applications and services. Therefore, many services and concepts related to smart grid such as Virtual Power Plant (VPP) [42] [43] and distributed energy and storage integration into the grid [44] are expected to require partial or fully distributed control and the ICT deployed in parallel to the electrical grid should be scalable and should not introduce additional constraints to the smart grid development. For this purpose, we plan to study and analyze the applications supported by NAN in order to define NAN communication requirements, and to implement an extension of GRACO that takes account of the QoS required.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies demonstrated that GPSR may generate significant overhead in the cases of multipoint-to-point (MP2P) and pointto-multipoint (P2MP) communications [13]. In a previous work [14], we proposed GRACO, a geographic routing protocol based on ant colonies that offers scalability, selfhealing and self-organization capabilities and supports MP2P, P2MP and point-to-point (P2P) communication modes with low complexity and overhead added compared to GPSR [15]. All these features make GRACO suitable for NAN.…”
Section: Introductionmentioning
confidence: 99%
“…In AMI, each smart meter is acting as router that forwards meter reading information to a central control centre. To obtain short, fast and reliable transmission, the position of the smart meter [6] is considered.…”
Section: Introductionmentioning
confidence: 99%